2017
DOI: 10.7860/jcdr/2017/24753.9739
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity Evaluation of Novel Nano-Hydroxyapatite-Silica Incorporated Glass Ionomer Cement

Abstract: Introduction: Glass Ionomer Cements (GIC) are among the most popular restorative materials, but their use in dentistry is limited due to their physical properties. The hardness of GIC was improved by incorporation of nano-hydroxyapatite-silica into GIC, to expand its applicability. Aim:To evaluate the cytotoxic effects of nano-hydroxyapatitesilica incorporated glass ionomer cement (HA-SiO 2 -GIC) on human Dental Pulp Stem Cells (DPSC) and compare it with conventional GIC and resin modified GIC. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
4
23
0
6
Order By: Relevance
“…These results are probably related to the composition. Bioactive materials promote Ca 2+ ion release, which has mitogenic effects on mesenchymal cells [24]. In contrast, Ionolux was cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…These results are probably related to the composition. Bioactive materials promote Ca 2+ ion release, which has mitogenic effects on mesenchymal cells [24]. In contrast, Ionolux was cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Most common formazan salts used to assess cell viability are MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium), XTT (2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide), WST-1, and WST-8 reagents [56,57,58,59,60]. The MTT/MTS test is widely used to assess the biocompatibility of CaPs [52,61,62,63]. Using the MTS method, Santos et al [52] showed that both chemically and hydrothermally synthesized HA did not affect the viability of MG63 cells treated for three and six days with HA concentrations lower than 500 μg/mL.…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%
“…Additionally, the addition of HANP to RMGIC may have decreased cytotoxicity due to chemical interaction, since HANP has a large amount of calcium and phosphorus ( Figure 2). Noorani et al [30], when analyzing the cytotoxicity of nanohydroxyapatite-silica, found that GIC interacted with HANP through the carboxylate groups in the polyacid [30], which can decrease the cytotoxicity of the material.…”
Section: Discussionmentioning
confidence: 99%